Aspirations, ambivalence, and performances: the hyphenated identities of Indonesian worker-students in South Korea. Issue 5 (3rd September 2018) - Nugroho, Suray; Cho, Younghan; Collins, Francis L.
ABSTRACT: This paper explores the lives of Indonesian migrant workers undertaking study through the Indonesia Open University in South Korea. Drawing on interviews, participant observation, and social media, the paper explores the rationales, experiences, and identity performances of these worker-students, placing emphasis on how these individuals challenge their socially constructed position as migrant workers. In doing so, the paper extends scholarship on the significance of migration in Asia and the way this is tied to the differential valuing of migrants, as low or high-skilled and workers or students. We draw particular attention to the transformative potential of migration but also the ways in which changes in subject position are negotiated in relation to existing social structures and identity positions. In the context of the focus on discrepant knowledge mobility, then, the paper shows how boundaries between types of migration are blurred through their connection with knowledge and the making of unexpected Inter-Asian connections.